PENINGKATAN KUALITAS PAUD DENGAN PROGRAM BERMADU DI KECAMATAN CIPARAY DUSUN ANDIR - Ari Abdul Kohar Rahmatullah, Ari Abdul Kohar Rahmatullah (Media Nusantara, 2023)
Quality includes aspects that influence the extent to which a product or service can satisfy user expectations. Improving the quality of Early Childhood Education (ECE) is very necessary to produce a golden generation that is quality and develops according to the expectations of parents and society. BERMADU is an abbreviation of learn, play together at posyandu. The method used in this research is descriptive qualitative. The data source used is primary data. The BERMADU program in Andir Hamlet, Ciparay District, shows a significant and sustainable positive impact on children's development and embraces the values of inclusivity and sustainability in the development of early childhood.